Effects of Foot-Core Training on Foot-Ankle Kinematics and Running Kinetics in Runners: Secondary Outcomes From a Randomized Controlled Trial - Matias, Alessandra B.; Watari, Ricky; Taddei, Ulisses T.; Caravaggi, Paolo; Inoue, Rafael S.; Thibes, Raissa B.; Suda, Eneida Y.; Vieira, Marcus F.; Sacco, Isabel C. N. (Frontiers in Bioengineering and Biotechnology, 2022)
This study investigated the effectiveness of an 8-week foot-core exercise training program on foot-ankle kinematics during running and also on running kinetics (impact loads), with particular interest in biomechanical outcomes considered risk factors for running-related injuries in recreational runners. A single-blind, randomized, controlled trial was conducted with 87 recreational runners randomly allocated to either the control (CG) or intervention (IG) group and assessed at baseline and after 8 weeks. The IG underwent foot-core training 3 times/week, while the CG followed a placebo lower-limb stretching protocol. The participants ran on a force-instrumented treadmill at a self-selected speed while foot-segment motion was captured simultaneously with kinetic measurements. After the intervention, there were statistically significant changed in foot biomechanics, such as: IG participants strike the ground with a more inverted calcaneus and a less dorsiflexed midfoot than those in the CG; at midstance, ran with a less plantarflexed and more adducted forefoot and a more abducted hallux; and at push-off, ran with a less dorsiflexed midfoot and a less adducted and more dorsiflexed hallux. The IG runners also had significantly decreased medial longitudinal arch excursion (p = 0.024) and increased rearfoot inversion (p = 0.037). The 8-week foot-core exercise program had no effect on impact (p = 0.129) and breaking forces (p = 0.934) or on vertical loading rate (p = 0.537), but it was positively effective in changing foot-ankle kinematic patterns.”